Sinergi Pemerintah, Lembaga, Dan UMKM Di Era Digital Melalui Konten Bincang Online - Limarandani, Ni Putu; Sabah, Kartika; Ketut, Anak Agung; Saisan, Made; Patera, A A Aditya Kusuma (Jurnal Pewarta Indonesia, 2024)
This study highlights the importance of synergy between government, institutions, and SMEs in the digital era through online discussion content, with a focus on the Terminal as the Local Economic Center in Pandeglang. Speakers from various relevant agencies, such as the Head of Terminal Management Section, Traffic Management & Engineering Division, and SME actors, provide insights into how the harmonization of central and regional government policies is crucial in implementing autonomy. The research emphasizes the significant role of information and communication technology in addressing the challenges of globalization, democratization, and decentralization. A qualitative case study method is used to demonstrate the importance of development communication through online discussion content to enhance synergy between government, institutions, and the public in responsive and transparent public services. New insights such as improving the competence of human resources in local government and the public, as well as expanding access to information networks, are crucial steps in addressing information technology gaps. In conclusion, synergy between government, institutions, and the public through effective communication and the utilization of information technology is key to building quality and inclusive public services in the era of regional autonomy. Keywords: The Digital Era; Content; development communication; public services; Government Synergy